2014
DOI: 10.15430/jcp.2014.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Non-Edible Plants as an Attractive Source of Compounds with Chemopreventive Potential

Abstract: Cancer remains a lethal disease, and many scientists are currently trying to develop more effective therapies. Natural compounds are potential sources of anti-cancer therapies and are obtained from diverse sources including marine organisms, microorganisms and plants. In this paper, we evaluated natural compounds from non-edible plant sources, which is a neglected area of research despite the promising future of these compounds. In addition, we assessed the function and mechanism of action of these compounds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Chemoprevention is the use of such agents which have potential to inhibit, reverse or retard tumorigenesis (Surh 2003). Use of natural plant products for cancer chemoprevention has gained considerable attention over the last few years (Surh 2003;Amin et al 2009;Ji et al 2014). Diet of people varies from place to place because of different lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…Chemoprevention is the use of such agents which have potential to inhibit, reverse or retard tumorigenesis (Surh 2003). Use of natural plant products for cancer chemoprevention has gained considerable attention over the last few years (Surh 2003;Amin et al 2009;Ji et al 2014). Diet of people varies from place to place because of different lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer chemoprevention with natural products, especially the phytochemicals present in various edible and non-edible medicinal plants, has received significant interest over the last several years. 1 , 2 The discovery and development of several clinically used anticancer drugs (e.g.,vincristine and paclitaxel) have been originated from plant sources. 1 A great deal of research on identifying chemopreventive phytochemicals has explored a large number of plant secondary metabolites, such as carotenoids, alkaloids, flavonoids, chalcones, xanthones, coumarins and terpenoids, with anticancer properties.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 The discovery and development of several clinically used anticancer drugs (e.g.,vincristine and paclitaxel) have been originated from plant sources. 1 A great deal of research on identifying chemopreventive phytochemicals has explored a large number of plant secondary metabolites, such as carotenoids, alkaloids, flavonoids, chalcones, xanthones, coumarins and terpenoids, with anticancer properties. 1 A large number of laboratory-based as well as epidemiological studies have demonstrated the cancer chemopreventive effects of rosemary ( R. officinalis L.), 3 a Mediterranean herb that is commonly consumed as diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extract after quantitative and qualitative analysis, could be used as a dietary supplement for astronauts, enriching the nutritional value of food. Before use the extract, will also be further purified, for example using chromatographic columns or filtration technique [14,16].…”
Section: Solid Waste Subsystemmentioning
confidence: 99%